Perancangan Sistem Pembangkit Listrik Tenaga Hybrid Antara PLN dan PLTS - Benediktus Boranpil Juen; I Wayan Suriana; I Wayan Sukadana; I Wayan Sugara Yasa (Jurnal Ilmiah Telsinas, 2020)
The need for energy in the world continues to increase while the fossil energy source used continue to run out, so an alternative energy is needed to supply energy needs. Electrical energy is an indispensable energy. The sun (sunlight) is one of the renewable energy, it can be used to generate electrical energy. Indonesia is a tropical country, so sunlight is available quite a lot. To get efficient and safe (consistent) electrical energy, you can use solar energy that is backed up with PLN's electrical energy (hybrid system). The planned hybrid system uses 200 WP (11 units) Solar panels, 100 Ah 12 V batteries (1 unit), Hybrid controller system with 1000 watt inverter, 12 Volt 10 A Charger Control. In use, charging the battery current for 6 hours. The way this hybrid system works is that the voltage is read using the INA219 voltage sensor, which will be processed on the Arduino Nano, and forward it to the relay to regulate the power source used, and display how much voltage is on the LCD. When the battery voltage runs out, usually at night, or the weather is cloudy, measured at 11.2 volts or below, the relay will switch the source from the battery (inverter) to the PLN source, the relay takes 1 second. And when the weather is sunny or the solar panel is exposed to a source of sunlight, measured at 12.0 volts or above, the relay will replace the power source from PLN to the battery (inverter), and the relay takes 1 second. Keywords: Hybrid System, Electric Power, solar panels